2008
DOI: 10.1097/hjh.0b013e328304b083
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of flow-mediated dilatation of the brachial artery in hypertensive patients

Abstract: The presence of endothelial dysfunction, as evaluated by flow-mediated vasodilatation of the brachial artery, identifies hypertensive patients at increased risk of nonfatal and fatal cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
68
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(75 citation statements)
references
References 40 publications
3
68
0
4
Order By: Relevance
“…Several clinical studies have shown that endothelial function assessed by FMD can serve as an independent predictor of cardiovascular events. 14,26,27 The present results, showing that endothelium-dependent vasodilation as measured by FMD appears lower in NSS subjects compared with NSR subjects, are consistent with previous measurements of forearm blood flow, 23 which further suggests that endothelium-dependent vasodilation is implicated in the development of salt sensitivity in humans.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several clinical studies have shown that endothelial function assessed by FMD can serve as an independent predictor of cardiovascular events. 14,26,27 The present results, showing that endothelium-dependent vasodilation as measured by FMD appears lower in NSS subjects compared with NSR subjects, are consistent with previous measurements of forearm blood flow, 23 which further suggests that endothelium-dependent vasodilation is implicated in the development of salt sensitivity in humans.…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Muiesan et al 26 assessed the technique of FMD as a measure of endothelial function in a group of 172 hypertensive patients at medium cardiovascular risk, which were followed up for fatal and non-fatal cardiovascular events. The results of that study showed that the incidence of cardiovascular events was more than double in those with compromised endothelial function, as defined by the cohort having an FMD value below the median.…”
Section: Discussionmentioning
confidence: 99%
“…5,10 Endothelial dysfunction has been clearly shown in essential hypertension and in patients at risk of atherosclerotic events, such as diabetics and patients with coronary artery disease. 1,2,5-8 Two independent studies measuring endothelial function in hypertensives, using acetylcholine-dependent forearm vasodilation 5 or the noninvasive flow-mediated dilation, 26 have suggested a worse cardiovascular prognosis in patients with a more impaired endothelial function, in a similar way as has been clearly shown in patients with coronary heart disease. 7,10 Endothelial dysfunction has a pivotal role in the development of atherosclerosis and cardiovascular diseases.…”
Section: Discussionmentioning
confidence: 94%
“…The most commonly used method to assess endothelial function in humans is flow-mediated dilatation (FMD), which measures the ability of the blood vessels to accommodate increases in flow by altering their internal diameter, and is dependent on nitric oxide (NO) release by endothelial cells. 62 Several studies document a direct independent relationship between the risk for cardiovascular events and the degree of brachial FMD in non-SCI individuals, [63][64][65] whereby the degree of cardiovascular risk is increased as the degree of brachial FMD is reduced.…”
Section: Conduit Arterial Function After Sci Structural Adaptationsmentioning
confidence: 99%